Sandiaga Uno : Personal Branding di Twitter - Deni Setiawan; Achmad Nurmandi (Jurnal Public Policy, 2020)
The development of communication technology has given birth to new media and social media. One of the potentials of social media is to form the personal branding of political actors. Personal Branding through Twitter social media accounts is becoming the current trend. This study aims to analyze Sandiaga Uno's Twitter account during the presidential and vice-presidential election campaign process in 2019. This study uses a qualitative approach to analyze secondary data on Personal Branding from Sandiaga Uno's Twitter account. As well as additional data from a literature study that discusses Personal Branding. Nvivo 12 Plus is used to analyze data. This study found that Sandiaga Uno used his personal Twitter to do branding during the campaign process, this can be seen from the content of photos, videos, and tweets that portrayed themselves as someone close to the community.